1970
DOI: 10.1002/jsfa.2740210211
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate content and amino acid composition of rapeseed (Brassica napus) meal as affected by sulphur and nitrogen nutrition

Abstract: Rapeseed plants have been grown in soil-free culture with varying amounts of nitrogen fertiliser applied as nitrate, and with 50% of the nitrate-N exchanged for ammonium. The experiment was performed at two levels of sulphate fertiliser. Yield, protein content, glucosinolate content and amino acid composition were studied. The glucosinolate content was lower and the protein content was higher at a high level of nitrogen fertiliser. Exchange of 50% of the nitrate-N for ammonium caused no significant change in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…The synthesis of cysteine as a result of the incorporation of sulphide moiety into O acetylserine appears to be the meeting point between N-and S metabolism. This result was corroborating with the findings of Josefsson (1970) who found that S fertilization had increased the Scontaining amino acids in rapeseed and Jarvan et al, (2008) reported an increase in cysteine and methionine content in wheat grain due to S fertilization.…”
Section: Methionine Contentsupporting
confidence: 90%
“…The synthesis of cysteine as a result of the incorporation of sulphide moiety into O acetylserine appears to be the meeting point between N-and S metabolism. This result was corroborating with the findings of Josefsson (1970) who found that S fertilization had increased the Scontaining amino acids in rapeseed and Jarvan et al, (2008) reported an increase in cysteine and methionine content in wheat grain due to S fertilization.…”
Section: Methionine Contentsupporting
confidence: 90%
“…In contrast, the study of Josefsson (1970) showed little variation in the relative proportion of both but-3-enyl and 2-hydroxybut-3-enyl among different S and N treatments. Both researchers used a chemical method (steam distillation, followed by titration and spectrometric determination) to quantify the alkenyl glucosinolates, which lacks both accuracy and precision.…”
Section: Discussionmentioning
confidence: 57%
“…5 and 7A) involved in the hydrolysis of glucosinolates to nitrile, sulfur, and sulfate (Wittstock and Halkier, 2002;Grubb and Abel, 2006;Kissen and Bones, 2009), which suggests an increased catabolism of these compounds in sultr3;4 developing seeds. Glucosinolates are transported from all parts of the plant into developing seeds, and most of the glucosinolates contained in oilseeds are located in the embryo (Josefsson, 1970;Gijzen et al, 1989). Their catabolism may release sulfate in the seed embryo for assimilatory pathways.…”
Section: Discussionmentioning
confidence: 99%